Assessment of 222Rn concentration and terrestrial gamma-radiation dose rates in the seismically active area - Baykara, O.; Inceoz, M.; Kulahci, F.; Dogru, M.; Aksoy, E. (Springer, 2008)
(222)Rn concentrations along the seismic active area (some distinct in East Anatolian Active Fault System (EAFS), Turkey) were determined by using passive and active (prompt) methods including CR-39 and Markus-10, respectively. It was observed that the changing of (222)Rn concentration along the fault lines, crossing the main East Anatolian Fault Line, has shown similar characteristics for both methods. The mean (222)Rn concentrations were found to be between 1.2 and 3.6 kBq.m(-3) and, 2 and 70 kBq.m(-3) by using passive and prompt methods, respectively. Nevertheless, some measured terrestrial gamma-radiation dose rate in the same area has weak positive correlation to (222)Rn concentration. Terrestrial gamma-dose rate at 1 m above the ground in the same sampling point, as for (222)Rn concentration measurement were made, varied from 8.5 to 10.6 mu R.h(-1).
Keywords: Radon Concentration; Soil-Gas; Turkey; Water